Does attention speed up processing? Decreases and increases of processing rates in visual prior entry. - Tünnermann, Jan; Petersen, Anders; Scharlau, Ingrid (Journal of Vision)
Selective visual attention improves performance in many tasks. Among others, it leads to 'prior entry'—earlier perception of an attended compared to an unattended stimulus. Whether this phenomenon is purely based on an increase of the processing rate of the attended stimulus or if a decrease in the processing rate of the unattended stimulus also contributes to the effect is, up to now, unanswered. Here we describe a novel approach to this question based on Bundesen’s Theory of Visual Attention, which we use to overcome the limitations of earlier prior-entry assessment with temporal order judgments (TOJs) that only allow relative statements regarding the processing speed of attended and unattended stimuli. Prevalent models of prior entry in TOJs either indirectly predict a pure acceleration or cannot model the difference between acceleration and deceleration. In a paradigm that combines a letter-identification task with TOJs, we show that indeed acceleration of the attended and deceler
Keywords: unattended stimuli; attention speed; cognitive processing; Attention; Humans; Judgment; Mental Recall; Visual Perception; Stimulus Parameters; Visual Perception; Visual Attention; Cognitive Processes; Velocity

Fachsensible Hochschuldidaktik - Scharlau, Ingrid (Teaching is touching the future: Academic teaching within and across disciplines)

Nur Zahlen und Zeichen? Zum Nutzen des Schreibens in der Hochschuldidaktik der Mathematik - Scharlau, Ingrid; Heß, Christiane; Schnieder, Jörn (Neues Handbuch Hochschullehre. 70. Ergänzungslieferung)

Reflection on the Leitmotif "Wrapped in Code" - Scharlau, Ingrid

Real-time Business Process Intelligence. Comparison of different architectural approaches using the example of the order-to-cash process. - Korotina, Anastasiia; Müller, Oliver; Debortoli, Stefan (International Conference on Wirtschaftsinformatik)
Business operations are becoming more and more integrated with the real-time intelligence. Core business activities are being carried out through OLTP systems that provide limited monitoring capabilities of the running process instances. The article shows how to turn the gap between the classic transactional system and the process-centric approach into an organization that provides more accurate and faster decisions on the strategic and operational management levels. This study aims at determination of what kind of information can be retrieved during the process execution and it tries to identify the need for the real-time process intelligence on the example of the order-to-cash process. Furthermore, we compare two architectural approaches of the real-time process intelligence monitoring system. The proposed frameworks retrieve process data from the ERP system in order to record crucial performance indicators on a real-time basis with the use of the in-memory technology.

Multi-Objective Storage Operating Strategy for Industrial Microgrids - Vogt, Thorsten; Fröhleke, Norbert; Böcker, Joachim; Kempen, Stefan (German-Korean Symposium on Power Electronics)

Mehrziel-Speicherbetriebsstrategie für industrielle Microgrids - Vogt, T.; Fröhleke, N.; Böcker, Joachim; Kempen, S.

Wortschatzsammler. Evidenzbasierte Strategietherapie lexikalischer Störungen im Kindesalter - Ulrich, Tanja; Motsch, H.J; Marks, D.K

Ein ausbildungsbezogenes Berufsfähigkeitsprofil für angehende Lehrkräfte im Bereich allgemeiner pädagogischer Kompetenz – ein Werkstattbericht - Seifert, Andreas; Israel, Georg; Bentler, Annette; Berning, Hanna; Bredt, Claudia; Buhl, Heike M.; Düsing, Elke; Eilerts, Katja; Günnewig, Kathrin; Trattwal, Hermann; Watson, Christina (Lehrerbildung auf dem Prüfstand)

Inwiefern sollten überfachliche Kompetenzen im Lehramtsstudium stärker gefördert werden? Eine interviewbasierte Studie - Bohndick, Carla; Kohlmeyer, Susanne; Buhl, Heike M. (Lehrerbildung auf dem Prüfstand)